Images of Tuva in Soviet Cinema of the 1930s (The Case of Boris Nebylitsky’s Creativity) - Golovnev, Ivan A. (The New Research of Tuva, 2021)
The article analyzes the phenomenon of the visual image of a region — the Tuvan People’s Republic (TPR) — during the transitional historical period that preceded its official incorporation into the Soviet Union. The author draws on the cases of “Beyond the Sayan Ridge” (“Za Saianskim khrebtom”) and “A Celebration in Tuva” (“Prazdnik Tuvy”) (1936), classic Soviet documentary films directed by Boris Rudolfovich Nebylitsky. These archival film documents are introduced into historical and anthropological discourse for the first time. The documentaries are studied and compared with the published memoirs of the director and thematically related materials by his contemporaries, as well as with the data on the sociocultural history of Tuva provided by researchers. On the one hand, these films captured information on the ethnography of Tuva that is valuable from a research point of view. On the other hand, they reflected contradictory images of the construction of the Soviet system in the Republic. The author examines the main plotlines of the film materials, which were made during the Tuvan expedition of Boris R. Nebylitsky and became the basis for the cinematic construction: “Traditional Tuva” (as an image of the dark past) and “Revolutionary Tuva” (as a prototype of a glittering future). The large-scale project “Cinema Atlas of the USSR” is considered as an external context of the creation of the film works. It was aimed at shooting news films about the Sovietization in the constituent republics, as well as in friendly regions and republics to popularize the achievements of the revolution and to present the Soviet territory as a multinational union of peoples liberated by the revolution. And the external actions of Tuvan party leaders aimed at introducing the Soviet model of development in the TPR are analyzed as an internal implication. It is concluded that the objective and subjective features of the considered films are multifaceted documents of the time. If researchers review them properly, these documentaries turn out to be insightful sources for studying both within Tuvan studies and in a wide range of thematically related branches of the humanities.